Vocational Training in the European Union - Mehmet BALCI (Yükseköğretim ve Bilim Dergisi, 2013)
European Union requires some standards in all areas. Today, the importance of training qualified individuals which holds an important place in the development of countries increases and certain standards are adopted creating common European Union tools in the field of vocational and technical education. In this study, vocational education and training policies system and the standards adopted by the European Union are discussed. Furthermore, this study was accepted as a European Union project in 2010 and the results obtained from the Leonardo Da Vinci Life Learning European Union project called “Web Based Basic Vocational Training” between the years 2010-2012 were presented. Since the partners of these projects are Turkey, Spain and Germany, the structure of vocational education, institutions of public and private vocational education and the diplomas and certificates entitled after these educations are included. As Turkey is on its way to become a European Union member, a number of advices are presented for Turkey to reach its destination about vocational education standards that European Union has aimed. The purpose of the study is not only to be a guide for the young who want to get professional training in the countries that are European Union members or candidates about how and where to have education opportunities but also to give a chance for trainers and training managers, participating in vocational training, so as to glimpse different practices from different countries and compare these practices between the countries of European Union and their countries. The study is also very important as it has the opportunities for training managers to see if their countries' vocational education is close enough to vocational education in European Union.